11-2x=5(x-5)+15

Simple and best practice solution for 11-2x=5(x-5)+15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-2x=5(x-5)+15 equation:


Simplifying
11 + -2x = 5(x + -5) + 15

Reorder the terms:
11 + -2x = 5(-5 + x) + 15
11 + -2x = (-5 * 5 + x * 5) + 15
11 + -2x = (-25 + 5x) + 15

Reorder the terms:
11 + -2x = -25 + 15 + 5x

Combine like terms: -25 + 15 = -10
11 + -2x = -10 + 5x

Solving
11 + -2x = -10 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
11 + -2x + -5x = -10 + 5x + -5x

Combine like terms: -2x + -5x = -7x
11 + -7x = -10 + 5x + -5x

Combine like terms: 5x + -5x = 0
11 + -7x = -10 + 0
11 + -7x = -10

Add '-11' to each side of the equation.
11 + -11 + -7x = -10 + -11

Combine like terms: 11 + -11 = 0
0 + -7x = -10 + -11
-7x = -10 + -11

Combine like terms: -10 + -11 = -21
-7x = -21

Divide each side by '-7'.
x = 3

Simplifying
x = 3

See similar equations:

| 28x^3-39x^2+12x-1=0 | | 9+5s-2=7-2s | | 2L-6=12-L | | x+(x+1)=77 | | 8(-24)+3=-48 | | 8x+3=-48 | | 15x^2-66x+24x=0 | | p=2(98)+2(102) | | 4x^2+64+220=0 | | 5x^2-3=27 | | 4x^2+20x=200 | | 18w-33=7w | | 3w^2+27w+54=0 | | 96=-16t^2+192t | | 21x^2-588=63x | | 16t^2-192t+96=0 | | x-32=530 | | 530=x+22 | | 10x+8-4=9x-4 | | 4x+3=7x+3 | | 16x^2+57x+49=x | | 3p^2-12q^2=0 | | 530=22-32+3x | | 7+4s-6=8s+5-3s | | 4s^2=s+1 | | -(8y+4)-(-7y-7)=-1 | | (2y-x+3z-13)-(4x+2-5y)+(6z+8)= | | 2.3-7x=-25.7 | | s^2=1+s(1-3s) | | (2bx+9x+4a)-(4bx-a)+(3b+a)= | | 6(3x-5)=3(6x+6) | | -2(q-4)=3q+12 |

Equations solver categories